EDUCATION ON ISLAMIC-BASED DIGITAL FINANCIAL MANAGEMENT TO PREVENT ILLEGAL LOANS AND FRAUDULENT INVESTMENTS AMONG GENERATION Z - Muhammad Ridwan; Ajwan Muddin; Hasbullah Hajar; Sajjaj Sudirman; Rahyuni Rahayu; Novadayanti Sune (Universitas Pattimura, 2026)
This program was developed in response to Generation Z’s limited understanding of digital financial risks, which necessitated an educational intervention integrating digital financial literacy with Islamic financial ethics. The program contributes a practical model for strengthening digital financial awareness among youth while demonstrating how Islamic values can guide safer and more responsible financial behavior. The activities were implemented through presentations, case-based discussions, and practical exercises, enabling participants to evaluate digital financial products and apply Islamic principles in financial decision-making. The results indicated a significant improvement in participants’ understanding, with post-test scores reaching 81.25%, reflecting a 32.5% increase compared to pre-test results, alongside positive responses and enhanced critical thinking toward legal and illegal financial services. In conclusion, the program effectively improved digital financial literacy while reinforcing ethical and Islamic financial values, highlighting the importance of sustaining similar educational initiatives for Generation Z.